The Afghanistan Mining Sector as a Driver of Sustainable Growth : Benefits and Opportunities for Large-Scale Mining - World Bank (Washington, DC, 2013)
This study attempts to quantify the benefits that could be obtained for the country of Afghanistan from the developments of the Aynak copper and Hajigak iron ore deposits and to discuss policies and programs-based on the experience of other countries-that will tend to maximize the benefits from these and other mines. In this study, the potential economic benefits to Afghanistan of its mining sector will be analyzed, focusing on the Aynak copper and Hajigak iron ore deposits. After an overview of the Afghan mineral industry and global trends in mining, a quantitative analysis will be made of the economic contribution of the development of these deposits and related infrastructure for income and employment in Afghanistan. Various scenarios will be presented as well as sensitivity analysis of key parameters. The analysis will focus on income, fiscal revenues, employment, sidestream linkages (sourcing), and the multiplier effects of expenditure by both the government and consumers. In the Afghanistan context, the mining sector is poised to be an important source of fiscal revenues, but it is likely just as important as an industry that can kickstart the industrialization process of the country and lead to broadly based inclusive growth. However, if the social and environmental costs of the mining operations are not managed properly, these benefits will not be sustainable in the long-term.